The King Shalmaneser (Šulmanu-ašarid) I: His Policy and his Military Campaigns - Abdul Malik, Munther Ali; Al-Ta'ee, Mohammad Hamza Hussein (Al-Adab Journal, 2021)
That the king of Shalmaneser (Šulmanu-ašarid) I (1274-1245 BC.) leave to us about 48 cuneiform Texts through which we were able to review the very important details about his life and the most important architectural, political and military achievements, most of these texts are too long and may be its lines reach to (30-60 lines), it is preceded by an introduction and he repeated it in most of his texts, perhaps he took it from his father's texts, Therefore, many similarities between his texts and his father's texts appeared in it. As for the second parts of his texts, it is alone in some paragraphs which was his own without other kings, it was not mentioned with the previous or successor kings, he also relied in some of his paragraphs on describing military events in the form of story narratives.